Pembuatan Batu Bata Dengan Memanfaatkan Abu Sisa Pembakaran Limbah Kayu - I Gede Oka Darmayasa (Jurnal Ecocentrism, 2022)
The wood processing industry in its production process will produce a waste or waste in the form of residual ash as a result of combustion in reducing the volume of waste that occurs. However, in the combustion process will produce a residue in the form of ash. The rest of this ash if not managed properly will cause pollution to the surrounding environment. One of the efforts made by utilizing the ashes from the combustion of wood waste as building materials is by using materials in a mixture of bricks. The research was conducted by mixing the remaining ash and clay in the proportions of 0%, 5%, 10%, 15%, 20% and 25%. From the results of the mixture tested the characteristics of the mixture such as compressive strength and water seepage. The results showed that the ash from the combustion of wood waste can be used as a material for making bricks as seen from the results of the physical characteristics test of the mixture.